Policy Implications to Improve the Business Environment to Encourage Female Entrepreneurship in the North of Vietnam - Anh, Nguyen Hoang; Tram, Hoang Bao (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
Abstract: Nowadays, Vietnamese women are participating actively in parts of the economy that were previously deemed male domain. Women are involved in business activities at all levels in Vietnam, making significant contributions to the economic development of the country. By December 2011, there were 81,226 small and medium enterprises headed by women, accounting for 25% of the total number of enterprises in the country (GSO, 2013). In Vietnam, despite recent economic development, socio-cultural and legal barriers are still very difficult for women since the general perception in society is that a woman’s main duty is to be a good housewife and mother and they are also often perceived as weak, passive and irrational (VWEC, 2007). Even though the studies related to women entrepreneurship development are quite extensive, amongst them only a limited number of researches on the role of legal and socio - cultural barriers on women entrepreneurs in the context of Vietnam have been investigated. Thus, supported by the World Trade Institute (WTI) in Bern, Switzerland, the researchers have chosen this as the subject of this study. Based on a quantitative survey of 110 companies in Hanoi and adjacent areas, the research has taken legal and socio - cultural barriers and explored their effect on the development of women entrepreneurship in the context of Vietnam in order to indicate how women entrepreneurs perceive the impact of socio-cultural factors, economic impacts, and policy reforms on their entrepreneurial situations and initiatives, and to then provide policy implications for promoting women’s entrepreneurship and gender equality in Vietnam. Keywords Entrepreneurship, female entrepreneurs, gender equality, Vietnam References Acs, Z. & Varga, A. (2005) ‘Entrepreneurship, agglomeration and technological change’, Small Business Economics, 24, 323---334. Avin, R.M & Kinney, L.P (2014). Trends in Female Entrepreneurship in Vietnam Preliminary paper presented at the 23th Annual Conference on Feminist Economics sponsored by IAFFE, University of Ghana, Accra, Ghana, June 27-29, 2014. Avin, R.-M., & Kinney, L. P. (2014) ‘Trends in Women entrepreneurship in Vietnam’, 23rd Annual Conference on Feminist Economics, Ghana: 27 – 29 June. Bruton, G. D., Ahlstrom, D., & Obloj, K. (2008). Entrepreneurship in emerging economies: where are we today and where should the research go in the future. Entrepreneurship: Theory and Practice, 32(1), 1–14. Bunck, J. M. (1997) Women and Post Cold War Socialism: the cases of Cuba and Vietnam, 7th Annual Meeting, Association for the Study of Cuban Economy, University of Miami, Knight Center, Hyatt Hotel, August 7-9 1997 Central Population and Housing Census Steering Committee (2010), The 2009 Vietnam Population and Housing Census: Completed Results, Statistical Publishing House, available at: http://vietnam.unfpa.org/webdav/site/vietnam/shared/Census%20publications/3_Completed-Results.pdf Chari, M. D., & Dixit, J. (2015). Business groups and entrepreneurship in developing countries after reforms. Journal Of Business Research,68, 1359-1366. Djankov, S. , R. L. Porta , F. Lopez-de-Silanes and A. Schleifer (2002) The Regulation of Entry, Quarterly Journal of Economics CXVII (1): 1-37 Food and Agricultural Organisation and United Nations Development Programme (2002) ‘Gender Differences in the Transitional Economy of Vietnam: Key Gender Findings – Second Vietnam Living Standards Survey, 1997 – 1998’. Vietnam: Food and Agricultural Organisation and United Nations Development Programme. Available at: http://www.fao.org/docrep/005/ac685e/ac685e00.htm [Accessed 7 December 2015]. Fuentelsaz, L., González, C., Maícas, J., & Montero, J. (2015). ‘How different formal institutions affect opportunity and necessity entrepreneurship’. Business Research Quarterly, 18(4), 246-258. Gallup, J (2004) The wage labor market and inequality in Vietnam. In Economic growth, poverty, and household welfare in Vietnam edited by Paul Glewwe, Nisha Agrawal, and David Dollar. Washington, D.C.: The World Bank. General Statistics Office of Vietnam (GSO) (2014), Population and employment Report 2014 Global Entrepreneurship Monitor. (2013). Vietnam report 2013. United Kingdom. Retrieved from: www.gemconsortium.org Hampel-Milagrosa, A., Pham, H., Nguyen, Q., and Nguyen, T. (2010) ‘Gender-Related Obstacles to Vietnamese Women Entrepreneurs’. Vietnam: United Nations Industrial Development Organisation and Vietnam Chamber of Commerce and Industry. Available at: http://www.un.org.vn/en/publications/publications-by-agency/doc_details/294-gender-related-obstacles-to-vietnamese-women-entrepreneurs. html [Accessed 7 December 2015]. Hang, T.T.T. (2008), “Women’s leadership in Vietnam: opportunities and challenges”, Signs, Vol. 34 No. 1, pp. 16-21. Hirschman, C. and V. M. Loi (1996) Family and Household Structure in Vietnam: Some glimpses from a recent survey, Pacific Affairs Vol 69 (No. 2 (Summer 1996)): 229-249 Hoang, B.T. (2010), “Rural employment and life: challenges to gender roles in Vietnam’s agriculture at present”, paper presented at the FAO-IFAD-ILO Workshop on Gaps, Trends and Current Research in Gender Dimensions of Agricultural and Rural Employment: Differentiated Pathways Out of Poverty Rome, 31 March-2 April 2009, available at: www.fao-ilo.org/fileadmin/user_upload/fao_ilo/pdf/Papers/16_march/Thinh_final.pdf Hoang, C., Hoang, C.L.T.S, Nguyen, T.P.C, Ngo, T.P.L, Tran, T.N, Vu, T.L (2013), The women’s access to land in contemporary Vietnam. UNDP Report 2013 Hoskisson, R. E., Eden, L., Lau, C.M., &Wright, M. (2000). Strategy in emerging economies. Academy of Management Journal, 43(3), 249–267. ILO (2011) ‘Creation of an enabling environment for women entrepreneur in Vietnam: Mainstreaming gender issues in government policy on enterprise development’, Hanoi. International Finance Corporation (2006) A National Survey of Women Business Owners in Vietnam. Joint survey with Gender and Entrepreneurship Markets (GEM) and the Mekong Private Sector Development Facility (MPDF), Washington, DC, IFC International Labour Organisation (2007) ‘Women’s Entrepreneurship Development in Vietnam’. Vietnam: International Labour Organisation. International Labour Organization and the Ministry of Labour, Invalids and Social Affairs of Vietnam (2010), The Informal Economy in Vietnam, ILO/MOLISA, Hanoi. Kibria, N. (1990) Power Patriarchy and Gender Conflict in the Vietnamese Immigrant Community, Gender and Society Vol 4 (No 1 (March 1990)): 9-24 Luke, N. , S. R. Schuler , B. T. T. Mai , P. V. Thien and T. H. Minh (2007) Exploring Couple Attributes and Attitudes and Marital Violence in Vietnam, New York, Sage Publications Mai thi Thanh Thai, Nguyen Hoang Anh (2016): The impact of culture on the creation of enterprises (2016), Journal for International Business and Entrepreneurship Development, Vol.9, No.1, pp.1 – 22 McChesney, F. (1987) Rent extraction and rent creation in the economic theory of regulation, Journal of Legal Studies 16 de Soto, H. (2000) The Mystery of Capital: Why capitalism Triumphs in the west and Fails everywhere Else, New York, Basic Books Minniti, M. (2010) ‘Women entrepreneurship and Economic Activity’, European Journal of Development Research, 22, pp. 294 – 312. Nguyen, B. (2011) ‘The Changes of Women’s Position: The Vietnam Case’, International Journal of Innovative Interdisciplinary Research, 1, pp. 126 – 138. Nguyen, B. (2012) ‘Abortion in Present Day Vietnam’, International Journal of Academic Research in Business and Social Sciences, 2 (1), pp. 56 – 61. Nguyen, C., Frederick, H., & Nguyen, H. (2014). Female entrepreneurship in rural Vietnam: An exploratory study. International Journal Of Gender And Entrepreneurship, 6(1), 50-67. Nijssen, E.J. (2014), Entrepreneurial Marketing: An Effectual Approach, Routledge, New York, NY. Raven, P., & Le, Q. (2015). Teaching business skills to women: Impact of business training on women’s microenterprise owners in Vietnam. International Journal Of Entrepreneurial Behaviour And Research, 21(4), 622-641. Rubio-Bañón, A., & Esteban-Lloret, N. (2015). Research article: Cultural factors and gender role in female entrepreneurship. Suma De Negocios Terrell, K., and Troilo, M. (2010) ‘Values and Women entrepreneurship’, International Journal of Gender and Entrepreneurship, 2 (3), pp. 260 – 286. Thanh, H.X., Anh, D.N. and Tacoli, C. (2005), “Livelihood diversification and rural-urban linkages in Vietnam’s red river delta”, Discussion Paper No. 193, International Food Policy Research Institute (IFPRI), available at: http://ideas.repec.org/p/fpr/fcnddp/193.html The World Economic Forum (2015) ‘The Global Gender Gap Report 2015’. Switzerland: The World Economic Forum. Available at: http://reports.weforum.org/global-gender-gap-report-2015/ [Accessed 8 December 2015]. Thi, L. (1995) Doi Moi and female workers: a case study of Ha Noi, in: V. M. Moghadam (ed.), Economic reforms, women's employment and social politics, Helsinki, World Institute for Development Research Tien, P. N. (2010) Overarching view of Gender Equality in Vietnam”, 2010, Conference on Commemoration of International Women’s Day 2010, “Beijing + 15, Looking back, reaching forward, Gender Equality and Women Empowerment 15 years after the Fourth World Conference on Women, Ha Noi, 12 March 2010. United Nations Development Programme (2012) ‘Women’s Representation in Leadership in Vietnam’. Vietnam: United Nations Development Programme. United Nations Development Programme (2015) ‘Human Development Report 2014’. USA: United Nations Development Programme. Available at: http://hdr.undp. org/en/content/human-development-report-2014 [Accessed 10 December 2015]. United Nations Industrial Development Organization (UNIDO). (2010). Gender related obstacles to Vietnamese Women Entrepreneurs. Vienna, Austria. Vietnam Women Entrepreneurs Council (2007) Women’s entrepreneurship development in Vietnam. International Labor Organization, Vietnam. Vuong, H., and Tran, D. (2009) ‘The Cultural Dimensions of the Vietnamese Private Entrepreneurship’, The IUP Journal of Entrepreneurship Development, 6 (3 & 4), pp. 54 – 78. VWEC (2007), Women’s Entrepreneurship Development in Vietnam, Vietnam Chamber of Commerce and Industry (VCCI) and the International Labour Organization (ILO) Report, Vietnam Women Entrepreneurs Council, available at: www.ilo.org/wcmsp5/groups/public/@asia/@ro-bangkok/documents/publication/wcms_100456.pdf Williamson, O. (2000) ‘The New Institutional Economics: Taking Stock, Looking ahead’, Economic Literature, 38, pp. 595 – 693. World Bank (2011a) ‘Vietnam Country Gender Assessment’. USA: World Bank. Available at: http://documents.worldbank.org/curated/en/2011/11/15470188/vietnam-country-gender-assessment [Accessed 7 December 2015]. World Bank (2011b). Vietnam development report 2012: Market economy for a middle- income Vietnam, Washington DC: The World Bank. World Bank (2012), Vietnam Country Gender Assessment, World Bank Country Office, Hanoi World Bank (2015), World Bank Database, Available at: http://data.worldbank.org/country/vietnam [Accessed 9 December 2015]. World Development Indicators (WDI) (2012), The World Bank, Washington, DC. Zhu, L., Kara, O., Chu, H.M.,Chu, A. (2015), ‘Women entrepreneurship: Evidence from Vietnam’, Journal of Business and Entrepreneurship, vol. 26, no. 3, pp. 103-128   lity in Vietnam.